Al-sunnah and future planning for social solidarity: A study on social charities organizations in Saudi and Turkey / Hanaa Abubaker Babateen - Hanaa , Abubaker Babateen (2016)
The study entitled “The Sunnah and Foreseeing of the Future in Social Solidarity- Charities- as a Model” addresses the prophetic guidance in foreseeing the future in social solidarity, in order to eliminate the social problems that hinder social solidarity in Islamic societies, and on the top is the poverty problem that facing some of world population. The first section the study aims to highlight the future rules that the Sunnah has established when it legalized social welfare means such as (zakat, charity, vows, atonements, wakf will, etc.) as well as highlighting the future rules that Sunnah has established in dealing with the beneficiaries of social solidarity such as (orphans, widows, divorcees, poor people and others), this can be done through foreseeing the prophet Mohammed (PBUH) Hadith from the six books, and stand on the annotations of these Hadith, and extract the most important benefits and lessons. The second section is intended to apply the future rules that have been highlighted in section I of the study on field for three charities in Saudi Arabia, specifically in Yanbu’ city, and other three charities in Turkey, in Istanbul in specific. Questionnaires were given to these charities divided into three axes, the first is the application on the future rules axis, and the second is the beneficiaries of social solidarity axis while the third one is the application on future goals axis. The parts of the questionnaire that fall under these axes are including some of the future rules. The data collected was analysed in various methods: Descriptive analysis, Normality test and Cronbach’s Alpha. The averages were calculated to know the extent of the application of these institutions to the guidance of the Prophet (PBUH) in foreseeing the future in social solidarity. The most significant results of this study: Extract (55) future rules of (65) prophetic Hadith regarding to means of social welfare, and extraction (87) future rules of (106) prophetic Hadith with regard to beneficiaries of social solidarity, The results of the field study were as follows: the application of the future rules was the highest percentage followed by the beneficiaries of social solidarity while the future goals was the lowest percentage, the results suggesting that the future planning of charities, and developing goals and plans for the coming years is weak among charities, and it needs more effort.